Impacts of extraction solvents and processing techniques on phytochemical composition and antioxidant property of mulberry (Morus spp.) leaves - Chiu-Hsun Liao; Hong-Xuan Fu; Kai-Hsiang Tu; Ji-Hong Zheng; Chia-Hung Shih; Yung-Sheng Lin (Cogent Food & Agriculture)
The novelty of this study is to comprehensively investigate the effects of various extraction methodologies, processing treatments, and leaf maturity on the quality attributes of mulberry leaf extracts. The findings indicated that extraction employing 70% ethanol or 100% methanol yielded the highest levels of bioactive compounds and greatest antioxidant activity, according to Fisher’s statistical least significant difference test. Specifically, the extraction efficiency of 70% ethanol under high-temperature conditions resulted in the highest efficiency, with total phenolic content reaching 60.1 ± 1.1 mg gallic acid equivalent/g dry weight, total flavonoid content at 14.8 ± 0.1 mg quercetin equivalent/g dry weight, DPPH scavenging ability of 447.8 ± 11.1 μg/mL (IC50), ABTS scavenging ability of 835 ± 6 μg/mL (IC50), and ferric-reducing antioxidant power of 41.1 ± 1.2 mg butylated hydroxyanisole equivalent/g dry weight. In the context of mulberry leaf processing, nonfermented leaves exhibited higher levels of total phenols and flavonoids and higher antioxidant potential than partially or fully fermented leaves did. Additionally, upper leaf segments of mulberry plants had higher levels of bioactive compounds and greater antioxidant activity than tender shoots.